STUDYING ATRIAL FIBRILLATION ON THE BASIS OF THE “PROFILE” REGISTRY - S. Yu. Martsevich; A. R. Navasardian; N. P. Kutishenko; L. Yu. Drozdova; A. V. Zakharova; N. V. Kiseleva (Кардиоваскулярная терапия и профилактика)
Aim. To research the prevalence of atrial fibrillation (AF) and to compare the clinical characteristics of the patients to those without AF.Material and methods. At the moment of cross-section the Profile Study included 671 patients with various cardiovascular diseases, those who consulted at the Preventive pharmacotherapy department of the Centre.Results. AF was diagnosed in 99 patients (14,7%). There was no difference by gender with those without AF, but they were significantly older. There was no difference in prevalence of the common risk factors, ischemic heart disease and peripheral atherosclerotic disease. Anamnesis of cerebral stroke was more common for the AF group: 9,1% vs 2,8%. Anamnesis of stomach ulcer disease was also more prevalent in AF group: 9,1% vs 4,4%.Conclusion. The section-study of patients included into Profile Registry showed typical clinical properties for AF and made it to compare with those found in other registries.